Phylogeographical analysis of Nerita yoldii revealed its geographical distribution pattern and drivers of population divergence in the Northwestern Pacific region - Yanbin Tang; Yanbin Tang; Yanbin Tang; Rongliang Zhang; Rongliang Zhang; Qinghe Liu; Qinghe Liu; Lu Shou; Lu Shou; Yibo Liao; Yibo Liao; Yibo Liao (Frontiers in Marine Science)
The distinctive tectonic settings and hydrological environments of the marginal seas in the Northwestern Pacific render them a focal point for investigating marine speciation and population diversity. In this study, we focused on understanding the phylogeography and demographic history of Nerita yoldii, a species commonly found in rocky intertidal areas. We examined the COI gene sequences from nine populations of the Northwestern Pacific. The analysis revealed four lineages comprising 35 haplotypes, with the majority of variation found within populations. Approximate Bayesian computation analysis supported the scenario that lineages B and C diverged first, and subsequently, lineage A and D originated from lineage C. Mismatch distribution analysis and neutrality tests suggested demographic expansion of lineage C primarily during the Pleistocene epoch of the Quaternary period, with expansion time estimated at approximately 38,000 years ago. Artificial rocky structures along the northern Changjiang coast, combined with global warming, could possibly facilitate the northward migration of N. yoldii larvae in recent decades. This has resulted in a shift in the species’ northern boundary. This study not only unveils the historical, present, and future impacts of climate and environmental changes on intertidal macrobenthos but also furnishes biological evidence crucial for comprehending related geological historical events. Moreover, it offers insights into the future trajectory of intertidal macrobenthos development and serves as a foundation for guiding future biological conservation efforts.